Educational Empowerment: Michelle Obama's Advocacy for Girls' Right to Education - Ramos López, Eva María (Frontiers in Law, 2025)
Michelle Obama, lawyer, writer, and former First Lady of the United States (2009-2017), has become a role model for women because of her beliefs in universal access to education. She has especially been a staunch defender of human rights and, in particular, of the rights of girls not only to access education, but also to remain in the system to access a university education that guarantees them a future and allows them to be independent. Unfortunately, this permanence in the educational system often entails a struggle against discriminatory social conventions based on gender, which lead girls to abandon their studies and, therefore, be relegated to the domestic-private sphere. In 2015, Michelle Obama and her husband launched Let Girls Learn to promote girls’ schooling and raise awareness of their need for higher education worldwide.